Selection and characterisation of tropical microalgae with high lipid content for enhancement of leucocytes viability in brown-marbled grouper, Epinephelus fuscoguttatus (Forsskal, 1775) - Yau, Sook Kun (2015)
In an aquatic ecosystem, microalgae are important primary producers which photosynthesise and supply essential nutrients such as proteins, lipids, vitamins and pigments to the higher trophic level fish and shellfish species. Brown-marbled grouper, Epinephelus fuscoguttatus (Forsskal, 1775) is one of the important marine finfish species that is commonly cultured in many Asian countries due to the rapid depletion of wild catches from the sea and yet unstoppable market demand. However till now, the pathogenic disease outbreak frequently occurs in grouper intensive farming and is still the main limiting factor in mariculture production. Immunonutrition using lipid is an environmentally friendly, safe and potential alternative approach to harmful antibiotics and other chemicals, which should be preferred and practiced in sustainable fish farming for fish disease control and prevention. Therefore, this study aimed to screen and select the best microalgae oil strain for in vitro enhancement of immune response in brown-marbled grouper based on their growth performance and lipophilic contents. Green microalgae consisting of Ankistrodesmus falcatus, Desmodesmus sp. and Scenedesmus sp. as well as diatoms including of Chaetoceros calcitrans, Cyclotella sp. and Skeletonema costatum were isolated and cultured in Bold’s Basal and Conway media respectively. After that, they were identified using a scanning electron microscope (SEM). Specific growth rate, total lipids, total carotenoids in lipid extract and fatty acid profiles of six microalgae species were characterised for screening and selection purposes. The selected microalgal lipophilic extract was further studied in immunonutrition of brown-marbled grouper in vitro using trypan blue exclusion (cell viability), bromodeoxyuridine (BrdU, lymphoproliferation) and respiratory burst assays. In this study, an optimised SEM pretreatment protocol with shorter chemical prefixation times (24 hours for Chaetoceros calcitrans; 3 hours for other examined microalgae species) and ideal separation forces (3 min at 3213 x g) was developed for all the selected microalgae species. Hence, they were successfully identified based on their unique ultrastructural, physical and morphological appearances which were clearly shown in high quality SEM images. Among microalgae species studied, Chaetoceros calcitrans had significantly higher (P < 0.05) specific growth rate (0.23 day-1) and total lipid (25.67% DW) and arachidonic acid contents (1.34% TIFA),whereas Ankistrodesmus falcatus showed the highest carotenoid (0.23 mg g-1 DW) and eicosapentaenoic acid contents (4.68% TIFA). In addition, two different microalgae lipids were rapidly grouped and identified based on their fatty acid biomarkers in principal component analysis (PCA) i.e. green microalgae lipid with MUFAs and C18-PUFAs as well as diatom lipid with SFAs and LC-PUFAs. Lipids derived from green microalgae and diatoms could be potentially used to fulfil the fatty acid requirements of farmed fish with and without C18-PUFAs bioconversion capability, respectively. Due to the outstanding traits (the highest total lipids with promising growth performance and the presence of LC-PUFAs), Chaetoceros calcitrans was selected for further evaluation of its immunonutrition value in brownmarbled grouper in vitro. Chaetoceros calcitrans lipophilic extract (CCLE) that ranged from 6.25 to 50 μg mL -1 significantly (P < 0.05) enhanced leucocyte viability isolated from peripheral blood of brown-marbled grouper compared to the control. Meanwhile, 3.13 μg mL-1 of CCLE had the lowest total viable leucocyte count that was not significantly different (P > 0.05) compared to the control. Therefore, four concentrations including 6.25, 12.5, 25 and 50 μg mL-1 of CCLE were selected and further tested in lymphoproliferation. Accordingly, 50 μg mL-1 of CCLE exhibited the highest stimulation index in both peripheral blood T and B lymphocyte proliferations of brown-marbled grouper stimulated by PHA and LPS respectively, whereas 6.25 μg mL-1 of CCLE was the lowest. This study also demonstrated that T lymphocyte proliferation performed better than B lymphocyte proliferation regardless of incubation with or without CCLE. On the other hand, only 6.25 μg mL-1 of CCLE had significantly higher respiratory burst activity in spleen leucocyte of brownmarbled grouper (P < 0.05) than the control. In conclusion, CCLE showed a potential to be used as an immunonutrient for enhancement of fish immunity, especially brown-marbled grouper. It is recommended that further in vivo studies should be conducted to examine the effectiveness of CCLE in an animal model.